“This Is How to Make a Good Medicine to Throw Away a Child Before It Even Becomes a Child”: The Maternal Voice in Jamaica Kincaid’s “Girl” and the Politics of Nature and Knowing in the Caribbean - O'Donnell, Rachel (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
This article argues that Jamaica Kinkaid’s short prose piece “Girl” (1978)—sometimes referred to as a poem, sometimes a short story—merits a rereading based on the politics of contraception and natural knowledge in the Caribbean. In sparse and delicate prose, Kincaid manages to reflect on the historical ability of women to be both creative and practical in managing the relationship between their bodies and the natural world. A central theme of the story is the often-overlooked disappearance of particular forms of knowledge in particular places. The story is also about how human knowledge can arise from necessity and can provide individuals and communities with both power and agency. One of the key lessons in the story links Kincaid’s characters to the Caribbean practice of resisting gender norms and colonialism through the use of plant-based abortifacients.